Event related potential responses to food pictures in hunger - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Electrophysiological signals originated from brain vary due to several conditions and our behavioral responses are effected by these conditions. In the daily life, hunger is one of states that we are frequently facing with. The aim of this study is to investigate the responses of brain by the use of Event Related Potentials when the subjects were hungry. Food and neutral images are used as stimuli and 16 channel EEG measurements are obtained from 11 volunteers. ERP amplitudes of occipital and right temporal area electrodes in 370 - 460ms after the stimuli were found to be greater for the food images than their values for right temporal side. Moreover, in that time window, wavelet coherence is used for ERP connectivity. Significant α and β band connectivity patterns were observed for occipito-frontal, parietal and fronto-temporal regions. © 2018 IEEE.
Keywords: coherence; connectivity; Event Related Potential